PEMBELAJARAN KOOPERATIF BERBASIS GAMIFIKASI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA: KAJIAN LITERATUR - Nurhafifah Asmad; Alya Eka Yatri; Asdar Asdar (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Mathematics learning is often perceived as a difficult and less engaging subject for students, which leads to low motivation and learning outcomes. This article aims to analyze the role of gamification-based cooperative learning in improving students’ motivation and mathematics learning outcomes. The method employed is a literature review by collecting and analyzing relevant scientific articles related to cooperative learning, gamification, learning motivation, and mathematics learning outcomes. The results of the review indicate that gamification-based cooperative learning consistently has a positive impact on students’ motivation and learning outcomes across various educational levels. The integration of group collaboration with game elements creates a more engaging, interactive, and student-centered learning environment. Increased learning motivation is reflected in higher student interest, active participation, and concentration during the learning process, which subsequently contributes to improved learning outcomes in the cognitive, affective, and psychomotor domains. In addition, the use of gamification platforms such as Kahoot, Quizizz, and other digital game-based media helps reduce learning boredom and encourages active student involvement. Based on these findings, the implementation of gamification-based cooperative learning strategies tailored to students’ characteristics and learning objectives is recommended to optimize the quality of mathematics learning. ABSTRAK Pembelajaran matematika sering dipersepsikan sebagai mata pelajaran yang sulit dan kurang menarik bagi siswa, sehingga berdampak pada rendahnya motivasi dan hasil belajar. Penelitian ini bertujuan untuk menganalisis peran pembelajaran kooperatif berbasis gamifikasi dalam meningkatkan motivasi dan hasil belajar matematika siswa. Metode yang digunakan adalah kajian literatur dengan menghimpun dan menganalisis berbagai artikel ilmiah yang relevan dengan topik pembelajaran kooperatif, gamifikasi, motivasi belajar, dan hasil belajar matematika. Hasil kajian menunjukkan bahwa pembelajaran kooperatif berbasis gamifikasi secara konsisten memberikan dampak positif terhadap motivasi dan hasil belajar siswa pada berbagai jenjang pendidikan. Integrasi kerja sama kelompok dengan elemen permainan mampu menciptakan suasana belajar yang lebih menarik, interaktif, dan berpusat pada siswa. Peningkatan motivasi belajar terlihat melalui meningkatnya minat, keterlibatan aktif, serta konsentrasi siswa selama proses pembelajaran, yang selanjutnya berdampak pada peningkatan hasil belajar pada ranah kognitif, afektif, dan psikomotorik. Selain itu, penggunaan media dan platform gamifikasi seperti Kahoot, Quizizz, dan media permainan digital lainnya membantu mengurangi kejenuhan belajar dan mendorong partisipasi siswa secara aktif. Berdasarkan temuan tersebut, diperlukan penerapan strategi pembelajaran kooperatif berbasis gamifikasi yang disesuaikan dengan karakteristik siswa dan tujuan pembelajaran agar kualitas pembelajaran matematika dapat ditingkatkan secara optimal.